2011
DOI: 10.1186/1471-2172-12-21
|View full text |Cite
|
Sign up to set email alerts
|

CTLA4 is expressed on mature dendritic cells derived from human monocytes and influences their maturation and antigen presentation

Abstract: BackgroundDendritic cells (DCs) initiate immune responses through their direct interaction with effector cells. However, the mechanism by which DC activity is regulated is not well defined. Previous studies have shown that CTLA4 on T cells regulates DCs function by "cross-talk". We investigated whether there is an intrinsic regulatory mechanism in DCs, with CTLA4 as a candidate regulator.ResultsWe confirmed via RT-PCR and flow cytometry the natural expression of CTLA4 on mature DCs derived from human monocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 37 publications
0
45
1
Order By: Relevance
“…In contrast to the well-known data suggesting lymphoid specificity, there also exist a number of inconclusive reports suggesting expression of CTLA-4 in myeloid lineage hematopoietic cells, including dendritic cells (DC) [23][24][25][26][27]. These sporadic data include a previous report of CTLA-4 mRNA expression from highly purified in vitro-derived myeloid DC [27].…”
Section: Introductionmentioning
confidence: 46%
See 2 more Smart Citations
“…In contrast to the well-known data suggesting lymphoid specificity, there also exist a number of inconclusive reports suggesting expression of CTLA-4 in myeloid lineage hematopoietic cells, including dendritic cells (DC) [23][24][25][26][27]. These sporadic data include a previous report of CTLA-4 mRNA expression from highly purified in vitro-derived myeloid DC [27].…”
Section: Introductionmentioning
confidence: 46%
“…Although a few sporadic reports previously hinted at myeloid lineage (i.e., DC) CTLA-4 expression, in normal immune homeostasis such reports were rare and largely inconclusive [24][25][26]. In this study, we present for the first time a thorough and conclusive characterization of DC CTLA-4 expression and function.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…These data are consistent with many studies reporting the ability of several immune cells to express both CD200R and CD200. Currently, the significance of co-expression of both receptor and ligand within the same cell population is unknown [50][51][52][53]. Because we found that the expression profiles of CD200 and CD200R on MSCs and T-lymphocytes were totally different, we then investigated the importance of the CD200-CD200R interaction in the inhibitory effects of MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to being expressed on T cells upon activation, CTLA-4 has been described to be expressed on activated B cells (18), monocytes (19), dendritic cells (20), and activated granulocytes (21). Although expression levels are lower than in T cells, CTLA-4 blockade in these cellular populations may be related to the in trans effects of ipilimumab treatment.…”
Section: Respectively) the Possibility Thatmentioning
confidence: 99%